Effect of hydrothermal pre-treatment (HTP) on poultry slaughterhouse waste (PSW) sludge for the enhancement of the solubilization, physical properties, and biogas production through anaerobic digestion. (June 2017) - Park, Seyong; Yoon, Young-Man; Han, Seong Kuk; Kim, Daegi; Kim, Ho
Highlights: HTP was shown to increase SCOD, VS and solubilization. The CST, TTF and particle size decreased with increasing HTP temperature. Methane yield increased with HTP until a temperature of 190 °C. Optimum operating temperature for HTP of PWSs was shown to be 190 °C. The application of the HTP could be enhancement for solubilization and anaerobic digestion. Abstract: This study is an assessment of the hydrothermal pre-treatment (HTP) of poultry slaughterhouse waste (PSW) sludge for the enhancement of the solubilization, physical properties, and biogas production through anaerobic digestion. This assessment was carried out to ascertain the optimal HTP temperature. The solubilization and physical properties efficacy was investigated by capillary suction time (CST), time to filter (TTF), and particle size. In addition, the anaerobic digestion was investigated through biochemical methane potential (BMP) tests and subsequent statistical analysis using the modified Gompertz model. HTP was found to have improved the solubilization of the PSW sludge with increasing HTP temperature. In addition, the results of the CST, TTF, and particle size decreased with increasing HTP temperature. These results of the assessment that was conducted in this study confirm that the HTP process indeed modifies the physical properties of PSWs to enhance the solubilization of organic solids. Nevertheless, the results of the BMP tests and the modified Gompertz model analysis show that the optimal HTP temperature of PSWs for anaerobic digestion is 190 °C. These findings show that to achieve high conversion efficiency, an accurately designed pre-treatment step must be included in the overall anaerobic digestion process for wastewater treatment.